2016
DOI: 10.1002/2016jd024879
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐nucleating particle emissions from biomass combustion and the potential importance of soot aerosol

Abstract: Ice‐nucleating particles (INPs) are required for initial ice crystal formation in clouds at temperatures warmer than about −36°C and thus play a crucial role in cloud and precipitation formation. Biomass burning has been found to be a source of INPs in previous studies and is also a major contributor to atmospheric black carbon (BC) concentrations. This study focuses on isolating the BC contribution to the INP population associated with biomass combustion. Emissions of condensation mode INPs from a number of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 41 publications
4
69
2
1
Order By: Relevance
“…Another potential INP source is local soil particles (Hill et al, ) lofted by increased winds associated with the landfalling storm. While some combustion sources, such as biomass burning, could also contribute to the INP population (Levin et al, ; McCluskey et al, ; Petters et al, ), Schill et al () found no emission of INPs from diesel combustion. Other anthropogenic emissions, such as sulfate and nitrate aerosol, while likely accounting for the majority of aerosol number in this region are not expected to contribute to the heterogeneous INP budget.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential INP source is local soil particles (Hill et al, ) lofted by increased winds associated with the landfalling storm. While some combustion sources, such as biomass burning, could also contribute to the INP population (Levin et al, ; McCluskey et al, ; Petters et al, ), Schill et al () found no emission of INPs from diesel combustion. Other anthropogenic emissions, such as sulfate and nitrate aerosol, while likely accounting for the majority of aerosol number in this region are not expected to contribute to the heterogeneous INP budget.…”
Section: Introductionmentioning
confidence: 99%
“…Observation of abundant BC in ice particle residuals in field experiments suggested that some BC-containing particles may preferentially act as INP (Cozic et al, 2008). In the experiments conducted by Levin et al (2016), emissions of different types of biomass fuel produced measurable concentrations of INP (0.1-10 cm −3 ) associated with higher BC concentration accounting for about 0-70 %. Determination of ice-nucleating properties of physically and chemically aged soot particles suggests that the heterogeneous ice nucleation activity of freshly emitted diesel soot particles is sensitive to some of the aging processes (Kulkarni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schill et al (2016) showed that neither fresh nor aged emissions from diesel engines contributed appreciably to atmospheric INP concentrations. However, some studies considered BC-containing particles as possible INP (Cozic et al, 2008;Levin et al, 2016;Cozic et al, 2007). Observation of abundant BC in ice particle residuals in field experiments suggested that some BC-containing particles may preferentially act as INP (Cozic et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements suggest that K-feldspar, a common component of soil dust aerosol, may account for a large fraction of Earth's INPs (Atkinson et al, 2013;YakobiHancock et al, 2013). Recent investigations of other aerosols have identified aromatic pollutant aerosols, secondary organic aerosols, marine aerosols, and aerosols produced from biomass burning as effective INPs DeMott et al, 2016;McCluskey et al, 2014McCluskey et al, , 2016Levin et al, 2016;Collier and Brooks, 2016).…”
Section: Introductionmentioning
confidence: 99%